The Effect of the Implementation of E-Invoice 3.0 and Taxable Person Compliance to Value Added Tax Revenue at KPP Pratama Pasar Rebo - Irawati Irawati; Hendra Darmawan; Muhammad Sofyan; Tatiana Serebryakova (Ilomata International Journal of Tax and Accounting, 2022)
Compliance of Taxable Person (PKP) is a complicated problem related to the implementation of an e-invoice application, especially the knowledge and perceptions of those who consider that making electronic-based tax invoices is difficult to do. This study aims to determine and analyze the effect of the e-invoice 3.0 application and Taxable Person compliance on the increase in VAT revenues. To obtain the research sample, the author used a non-probability sampling technique with the convenience sampling method. The results showed that e-invoice 3.0 implementation and Taxable person compliance simultaneously had a positive and significant effect on VAT revenues with a value of 113,819. The author provides suggestions for the Primary Tax Office of Pasar Rebo, Jakarta to continue improving its services in providing information and campaign related to the use of e-invoice 3.0 to Taxable person to improve their compliance and also to increase the amount of tax revenue which can affect VAT revenues.